El agua edáfica en la definición de micrositios para los primeros años de plantación de clones de Populus sp - Baridón, Juan Esteban (2005)
The aim of this work was to determine the incidence of the edaphic water in the microsites definition during the first years of Populus spp clones plantation. An essay with stakes of Populus deltoides cv. "Stoneville 66 and P. x euramericana cv. "Conti 12" was implanted, in three micro-reliefs of a Typic Hapludol of Buenos Aires, Argentina; using total height to the 6 and 20 months like variable response. In each micro-relief and depth, the water content was determined to: 33; 101; 505 and 1515 Kpa of tension and the hydric retention curves. The tension of retained water was calculated during the growth period. In February, with hydric deficit of 5 mm, the “Lower micro-relief” retained water to inferior tensions of 122 Kpa, the “Middle micro-relief” of 454 Kpa and the "Upper micro-relief " more than 1515 Kpa. Conti 12 didn't present differences of height between micro-reliefs. Stoneville 66 manifested significant differences comparing Upper-Middle with Lower microrelief. The differential retention of edaphic water of the hydric deficit periods determined, for Stoneville 66, the microsites existence.